Regional variation in ongoing sound change: The case of the Dutch diphthongs. Issue 2 (October 2021) - Voeten, Cesko C.
Abstract: This paper discusses the regional variation in four ongoing sound changes in the Dutch vowels /eː, øː, oː, ɛi, œy/ that are conditioned by a following coda /l/. The synchronic diatopic diffusion of these changes is charted using the Dutch teacher corpus, a comprehensive dataset containing word-list data from four regions in The Netherlands and four in Flanders. Comparisons are made of the five vowels preceding nonapproximant consonants and preceding coda /l/. To avoid manually segmenting the oftentimes highly gradient vowel–/l/ boundary, GAMMs are used to model whole formant trajectories. Comparisons are then made of trajectories and of peaks of trajectories. The results are used to classify the nature of the four sound changes in terms of phonetic and lexical abruptness/graduality and to show that the changes are intertwined in such a way that they can only be considered as separate facets of a single, currently ongoing vowel shift.